The many facets of the Fabry–Perot. (20th September 2016) - Sánchez-Soto, Luis L; Monzón, Juan J; Leuchs, Gerd
Abstract: We address the response, both in amplitude and intensity, of a Fabry–Perot from a variety of viewpoints. These complementary pictures conspire to achieve a comprehensive and consistent theory of the operation of this system.